Heart rate variability: a multidimensional perspective from physiological marker to brain-heart axis disorders prediction - Liu, Shujuan; Cui, Yunyi; Chen, Meihong (Frontiers in Cardiovascular Medicine, 2025)
Heart rate variability (HRV), a non-invasive measure of autonomic nervous system (ANS) activity and homeodynamics, has received much attention in recent years in the study of cardiovascular disease, mental health, and aging. Changes in HRV not only reflect an individual's ability to adapt to changes in the internal and external environment but also correlate with a wide range of pathological states, making it a powerful tool for predicting disease risk and assessing the efficacy of treatment. The aim of this review is to comprehensively analyze the role of HRV in different physiological and pathological contexts and explore its value as a potential biomarker. Initially, we review the basic concepts, measurements, and influencing factors of HRV, followed by an in-depth discussion of the relationship between HRV and cardiovascular disease, epilepsy, depression, aging, and inflammation. Special emphasis is placed on the role of HRV in assessing the health impact of obesity, nutrition, and lifestyle. Additionally, we explore the use of HRV in clinical practice, including its potential in predicting disease, guiding treatment, and evaluating the effects of interventions. Ultimately, we suggest future research directions, including the promise of HRV in individualized medicine and health monitoring. While HRV holds promise as a non-invasive, trans-diagnostic biomarker, current evidence remains preliminary and largely associative. Its clinical utility for personalized medicine or routine risk prediction requires standardized acquisition protocols, external validation, and causal inference studies before implementation into decision-making algorithms. By synthesizing multiple studies through the lens of brain - heart axis (BHA) integrity, we propose that HRV metrics serve as a quantifiable, trans-diagnostic proxy for mapping the measurement, mechanistic, and translational axes of brain - heart dysfunction.